ANALISIS PENERAPAN AKUNTANSI LINGKUNGAN PADA INDUSTRI TEKSTIL YANG TERDAFTAR DI BEI - Irmaviyanti, Cut; Afrianandra, Cut (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2024)
Currently, the problem of environmental damage has become a public concern. Textile companies are a significant source of environmental pollution due to the trash they generate throughout their production activities. Accounting contributes to environmental preservation by incorporating voluntary disclosure of environmental costs or expenses in financial statements. However, there is no standardized approach to environmental accounting disclosures within the PSAK.The study examines environmental cost accounting in 20 BEI-registered textile companies' financial statements or annual reports. The data comes from BEI-registered textile companies' annual financial statements. The study examined textile manufacturers' yearly accounting implementation using qualitative descriptive methods. Based on their corporate annual reports' CSR sections, only 10 out of 20 textile businesses have incorporated environmental accounting. Only 4 out of 10 corporations disclose their environmental expenditures in their financial or annual reports.